PERENCANAAN JARINGAN LONG TERM EVOLUTION (LTE) PADA FREKUENSI 700 MHZ DI AREA KOTA KEDIRI BERDASARKAN COVERAGE DAN CAPACITY MENGGUNAKAN SOFTWARE ATOLL RADIO PLANNING - Abdillah, Ginanjar Fahmi; Kusmaryanto, Sigit; Sari, Sapriesty Nainy (Jurnal Mahasiswa TEUB, 2024)
LTE is an Internet Protocol (IP) based technology with increased speed and spectrum efficiency compared to previous technologies. The 700 MHz frequency is the most ideal frequency for LTE in Indonesia. This is based on wider coverage, wide bandwidth availability, and smaller propagation loss compared to other frequencies. Determining the number of sites to be used refers to coverage calculations and capacity dimensioning. Then the location is chosen based on the existing site location in Kediri City so as to minimize blank spot areas. Then this planning uses Atoll Radio Planning software with the Okumura-Hatta propagation model. Dimensioning calculations show that the number of eNodeBs needed in this plan is 23 eNodeB sites. The simulation results show that the plan has a Received Signal Strength Indicator (RSSI) value of -66.36 dBm with a signal level that is categorized as good, namely >-90 dBm capable of covering an area of 65.62 km2. The average Reference Signal Receiver Power (RSRP) value obtained is -98.98 dBm. The average throughput value obtained was 22.354 Kbps. Keywords: LTE, Atoll, RSSI, RSRP, Throughput